PEMAHAMAN KONSEP MATEMATIKA PADA MATERI PERKALIAN - Nurhasmiranti; Jesi Alexander Alim (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2023)
This study aims to determine the ability to understand the concept mathematics of 6th grade elementary school students in multiplication material, knowing the difficulties experienced by students in understanding mathematical concepts in multiplication material, knowing the factors that influence students' difficulties in understanding multiplication material. This type of research uses qualitative. The subjects used in this study were 6th grade students. The research was conducted by researchers on a small scale, with a total of 5 students consisting of 2 male students and 3 female students. Data collection tools used tests, observations and interviews. This research data analysis technique namely interactive analysis which includes data collection, data presentation and drawing conclusions. The results of this study indicate that there is3 students who understand the concept of multiplication and 2 students who do not understand the concept of multiplication. The difficulties faced by students are forgetting the basics of multiplication that have been memorized and students not being able to convert multiplication into repeated addition in the form of pictures. The difficulties faced by students were caused by students not understanding the concept of multiplication and students using rote methods to learn multiplication.